Blocking K-Ras Interaction With the Plasma Membrane Is a Tractable Therapeutic Approach to Inhibit Oncogenic K-Ras Activity - Henkels, Karen M.; Rehl, Kristen M.; Cho, Kwang-jin (Frontiers in Molecular Biosciences, 2021)
Ras proteins are membrane-bound small GTPases that promotes cell proliferation, differentiation and apoptosis. Consistent with this key regulatory role, activating mutations of Ras are present in ~19% of new cancer cases in the U.S. per year. K-Ras is one of the three ubiquitously expressed isoforms in mammalian cells, and oncogenic mutations in this isoform account for ~75% of Ras-driven cancers. Therefore, pharmacological agents that block oncogenic K-Ras activity would have great clinical utility. Most efforts to block oncogenic Ras activity have focused on Ras downstream effectors, but these inhibitors only show limited clinical benefits in Ras-driven cancers due to the highly divergent signals arising from Ras activation. Currently, four major approaches are extensively studied to target K-Ras-driven cancers. One strategy is to block K-Ras binding to the plasma membrane (PM) since K-Ras requires the PM binding for its signal transduction. Here, we summarize recently identified molecular mechanisms that regulate K-Ras PM interaction. Perturbing these mechanisms by pharmacological agents blocks K-Ras PM binding and inhibits K-Ras signaling and growth of K-Ras-driven cancer cells. Together, these studies propose that blocking K-Ras PM binding is a tractable strategy for developing anti-K-Ras therapies.